Asymmetry in steel welds with dissimilar amounts of sulfur. (November 2015) - Wei, H.L.; Pal, S.; Manvatkar, V.; Lienert, T.J.; DebRoy, T.
Graphical abstract: During welding of steels containing dissimilar amounts of sulfur, the weld pool is shifted laterally from the original joint interface and rotated at an angle with the interface as shown in the figure below. We show for the first time that Marangoni convection causes these rotational and translational asymmetries and the reported arc shift is a consequence of asymmetric melting rather than its cause. Abstract: During welding of steels containing dissimilar amounts of sulfur, the weld pool is shifted laterally from the original joint interface and rotated at an angle with the interface. The mechanism for this unusual behavior is not known. Here, we show for the first time through comparison of numerically calculated and experimental results that Marangoni convection causes these rotational and translational asymmetries and the reported arc shift is a consequence of asymmetric melting rather than its cause.